Influences of visitors motivation on decision making: A case study on Petrosains Discovery Centre / Noor Suziera Shakri - Shakri, Noor Suziera (Bachelor of Science (Hons) Statistics, 2014)
The effective of the tourism marketing is impossible without an understanding of the tourist’s motivation. Motivation plays a very important role in the process of decision making of travelling for marketing reasons as well as in the process of formation of partnership with other area. The purpose of this study is to identify the influence of visitor motivation on the decision making process. A single cross sectional design was applied to identify the factors that influence visitor decision making among the visitors at Petrosains Discovery Centre. The total of 244 survey questionnaires was collected by using convenience sampling method. The sample size of 149 respondents was selected from all seven categories out of 244 populations by using stratified sampling. The factors studied were socio demographics, learning factor, novelty, social interaction, experience seeking and professional interest. Descriptive analysis, correlation analysis and multiple linear regressions were used to analyze the data in order to meet the objectives. The study found that gender and age has no significant influence in median to visitor decision making. Meanwhile, type of visitor and category of the visitor showed a significant difference toward decision making. The correlation analysis showed a significant association between learning, novelty, social interaction, experience seeking and professional interest to decision making. In the multiple linear regression analysis, the result showed that only learning, novelty and social interaction gave a significant value which (p=0.000< 0.05). The fact that science centre visitors are primarily motivated to attend for social interaction reasons as well the fact that science centre is a place where people motivated to go for learning. This study also proved that people go to the science centre for novelty, and that even though they were not primary motivation, this factor was still prevalent in these visitors